Surveillance, prevention, and control of vector-borne diseases 2 - Day, Jonathan (Henry Stewart Talks, 2021)
Secondary host surveillance, Human transmission patterns, Syndromic surveillance, Environmental surveillance, Early warning of potential outbreaks compared to biological surveillance, Rainfall and drought cycles, Temperature, Prevention and control